2018
DOI: 10.1097/jxx.0000000000000139
|View full text |Cite
|
Sign up to set email alerts
|

Beyond competencies: Practice standards for emergency nurse practitioners—A model for specialty care clinicians, educators, and employers

Abstract: Background/purpose: The growth of advanced practice nursing specialties requires additional expertise for practice that goes beyond entry-level competencies, knowledge, skills, and abilities. A practice standards model for specialty nurse practitioners (PSMSNPs) is introduced that differentiates entry-to-practice population foci competencies from advanced specialty practice standards. Objectives: (a) Differentiate competencies and practice standards in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 11 publications
1
7
0
Order By: Relevance
“…The lowest self-assessment score obtained was related to the quality assurance field. These findings are similar to the results presented by Faraji et al (2019) [20]. Thus, it is necessary to train nurses how to use new research findings in a clinical setting and to observe improvements among the nurses working in emergency departments because this matter is connected to the four areas of expertise (i.e., the use of clinical research, the assessment of patient care, the use of research findings in nursing care, and the ability to identify areas related to care), all of which need to be upgraded and evaluated.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The lowest self-assessment score obtained was related to the quality assurance field. These findings are similar to the results presented by Faraji et al (2019) [20]. Thus, it is necessary to train nurses how to use new research findings in a clinical setting and to observe improvements among the nurses working in emergency departments because this matter is connected to the four areas of expertise (i.e., the use of clinical research, the assessment of patient care, the use of research findings in nursing care, and the ability to identify areas related to care), all of which need to be upgraded and evaluated.…”
Section: Discussionsupporting
confidence: 93%
“…Although Karami et al (2017) found no significant relationship between the mean self-assessment of nurses with marital status and education level, their results indicate that the mean score of the professional competency of married nurses was higher than that of single nurses [20]. Regarding this matter, professional promotion and nursing competency appear to be affected by personal, socioeconomic, and cultural factors [20].…”
Section: Discussionmentioning
confidence: 91%
“…These findings are similar to the results presented by Faraji et al (2019) (16). Thus, it is necessary to train nurses how to use new research findings in a clinical setting and to observe improvements among the nurses working in emergency departments because this matter is connected to the four areas of expertise (i.e., the use of clinical research, the assessment of patient care, the use of research findings in nursing care, and the abil- ity to identify areas related to care), all of which need to be upgraded and evaluated (17).…”
Section: Discussionmentioning
confidence: 99%
“…As pharmacists pursue national provider status, it is important to demonstrate competency through appropriate documentation of licensure and certification. Having a centralized platform to document professional qualifications and practice history may positively contribute to the advancement of the profession similar to platforms used by other healthcare professionals 34 to justify billing and reimbursement of patient care services. The results from this study demonstrate the market need and demand for an integrated credentialing system; as well aspractitioner willingness and interest in adopting such a system.…”
Section: Discussionmentioning
confidence: 99%